Organisational Change Management: A Case Study of Bristol Customer Service Centre: Evaluation and Recommendations - Upadhyay, Angeli (2006)
Change in today's economy is pervasive, continuous and often a rapid process. Since change has become a ubiquitous part of organisational dynamics, employees who resist change can be a detriment to the effective running of the organisation.